Comparative Analysis of Rainfall Estimation Methods Using Observation Data and Satellite Data in Coastal Areas of Kalimantan Barat Province - Triono, Reno; Utomo, Kiki Prio; Jati, Dian Rahayu (Fakultas Teknik Universitas Tanjungpura, 2024)
This study analyzes the accuracy of satellite rainfall data compared to observed data at several stations in West Kalimantan from 1998 to 2019. Three methods